Effect of serum from laying hen and antiprolactin drug on egg production of indigenous chicken in Bangladesh - Parvez, Misrat Masuma; Islam, Rakibul; Rashid, Bazlar; Hasan, Mahmudul; Mobarak, Hosne; Roy, Kishor Kumar; Haque, Md Anowarul (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was carried out to improve egg production by decreasing the inter sequence pause days in indigenous chicken through the use of antiprolactin agent (Bromocriptine) and serum from laying hen. Sixty indigenous (deshi) chickens of 20-22 weeks of age, were randomly assigned into four groups (A, B, C and D) and each group consisting of 15 hens. Group A designated as control, group B was treated with Bromocriptine orally at a dose of 640 μg/bird/day, group C was treated with serum of laying hen at a dose of 1 ml intramuscularly/bird/day and group D was treated with both serum and Bromocriptine at doses given to group B and C for the period of 15 March, 2015 to 16 June, 2015 and egg production, pause days, prolactin level, hematological parameter and egg qualities were observed. Egg production increased significantly (p<0.05) in all treated groups compared to the non- treated control group and the highest production was recorded in group D. Pause days and prolactin levels decreased significantly (p<0.05) in all treated groups and lowest were recorded in hens of group D. No significant (p>0.05) differences were observed in hematological values among the group of chicken. The present study reveals that combined treatment with Bromocriptine and serum from laying hen increases egg production without affecting the health of indigenous chickens. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 51-54